The market for leather goods in North America and selected western European countries - International Trade Centre UNCTAD/GATT. (Geneva : International trade Centre., 1969)
The main purpose of the survey is to find ways and means of promoting exports from developing countries by studying the prevailing market situation in the countries selected. The study is intended primarily for countries where exports of leather goods are planned or have just started.
Bibliography: p. 300-302.
rpm 21/01/2019
Loans
Keywords: Leather industry and trade; Leather industry and trade